Penyuluhan Cuci Tangan Pakai Sabun Di Kelurahan Margorejo Dalam Upaya Pencegahan Penyebaran Covid-19 - Nurul Mahmudah; Atina Mirawati; Muhammad Syakir Alkautsar (JPM: Jurnal Pengabdian Masyarakat, 2021)
: Until now, the world is still shocked by the Covid-19 virus pandemic, including Indonesia. In Indonesia alone, positive cases of Covid-19 have reached 1.2 million people with the number of deaths reaching 32,656 people and 1 million people have been confirmed cured. One way to prevent virus transmission is to wash your hands with soap in accordance with established rules or protocols. Washing your hands frequently and in an appropriate manner (for at least 40 seconds) is one of the most important steps to prevent COVID-19 infection. The purpose of this outreach activity is to support the government to prevent the spread of Covid-19 by implementing washing hands with soap and providing understanding to children about the importance of washing hands. The research was conducted by giving materials to children and the practice of washing hands using soap in running water to the children of RW 01 and providing a place to wash hands in front of the posko as an example of implementing hand washing. This activity was carried out so that children were aware of the dangers of Covid-19 and so they could anticipate the spread of Covid-19. This activity can also have a positive impact on children so that they can implement hand washing activities with soap in their daily lives. There are still children who do not know and memorize the steps for washing hands with soap.